One Dimensional Cutting Stock Problem (1D-CSP): A New approach for Sustainable Trim Loss - Powar, P. L; Samuel, Siby (International Journal of Computer Sciences and Engineering, 2025)
Given the stock lengths , this paper computes the total trim loss of One-dimensional-cutting stock problem (1D-CSP) by considering the cutting plan of at most two order lengths at a time of the required order lengths . The Total Trim Loss (TTL) is computed by fixing a variable as the percentage of the Pre-Defined Sustainable Trim Loss(PDSTL) on the given stock by the industry. In view of the past experience, it has been noticed that the trim loss up to 3% is viable for the smooth running of the industry. Hence, we consider 3 as the upper bound of the pre-defined sustainable trim t. Considering the variable with the stepping of as the nodal points in the domain, we have first computed the corresponding TTL and plotted these points in the range. With this information, Lagrange Interpolation method has been applied to predict the TTL at any arbitrary point .